Differential fertility, school enrollment, and development - Jie Zhang; Haoming Liu (Journal of Population Economics, 2023)
This paper develops a model wherein parents choose the number of children, enroll some children in school at indivisible education costs, and receive supplemental earnings from uneducated children. The model accounts for the positive relationship between enrollment ratios and parental earnings and the N-shaped relationship between fertility and parental earnings in Brazil and Indonesia. When children's living costs are high (low) relative to education costs and children's earnings, fertility increases (decreases) with parental earnings due to a dominant income (substitution) effect. A decline in the ratio of child earnings to parental earnings or a rise in education subsidy rates can increase enrollment ratios and decrease fertility. Under progressive income taxes and favorable education subsidies for poor families, educated parents' fertility could be higher than that of illiterate parents' when incomes are low. However, the relationship will be reversed partially because of the rising education subsidy.
Keywords: I24; J13; O10; 330; School enrollment; Fertility differential; Growth; Demographic transition